1984
DOI: 10.1104/pp.75.4.1158
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of the Poly-β-Hydroxybutyrate and Citric Acid Cycles of Rhizobium japonicum Bacteroids

Abstract: ABSTRACrThe activities of several enzymes of the citric acid and poly-4e-hydroxybutyrate cycles were measured in Rhizobiumjapeoicwm 3IIB-143 bacteroids which had been isolated from soybean nodules by sucrose gradient centrifupaton. Duing the period of developing nitrogenase activity, the specfic activity of fumuase, hydroxybutyrate dehydrogenase, ,-ketothiohlse, and pyruvate dehydrogenase complex incesed whereas acetoacetate-succinyl-CoA transferase and isocitrate dehydrogenase decreased (2,8,9,15,17,21,25,28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
76
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 22 publications
7
76
1
Order By: Relevance
“…The inside of the nodules is believed to be anaerobic, and an anaerobic carbon metabolism S ,9) and poly-j1-hydroxybutyrate metabolism were already reported. 10 ,11) Though these results suggest a complicated carbon metabolism in the nodules and the bacteroids, no attempt has been made to elucidate how the organic acids are metabolized and how they generate ATP and reducing power for the nitrogenase system. Recently an anaerobic rapid isolation technique was employed to obtain bacteroids retaining high ARA,12) and this procedure was supposed to have been very reliable in studying the relationship between carbon metabolism and nitrogen fixation in bacteroids.…”
mentioning
confidence: 99%
“…The inside of the nodules is believed to be anaerobic, and an anaerobic carbon metabolism S ,9) and poly-j1-hydroxybutyrate metabolism were already reported. 10 ,11) Though these results suggest a complicated carbon metabolism in the nodules and the bacteroids, no attempt has been made to elucidate how the organic acids are metabolized and how they generate ATP and reducing power for the nitrogenase system. Recently an anaerobic rapid isolation technique was employed to obtain bacteroids retaining high ARA,12) and this procedure was supposed to have been very reliable in studying the relationship between carbon metabolism and nitrogen fixation in bacteroids.…”
mentioning
confidence: 99%
“…Malate dehydrogenase and hydroxybutyrate dehydrogenase were chosen for this type of analysis because of their different developmental profiles (9). Malate dehydrogenase activity remained unchanged during nodule development, whereas hydroxybutyrate dehydrogenase increased at least 3-fold over the same time period (9). Ching et al (3) had reported that the latter activity was 2.5 times greater in the mature bacteroid fraction than in the bacterial fraction.…”
mentioning
confidence: 99%
“…However, numerous biochemical changes have been reported during symbiotic development. These include alterations in enzyme levels, DNA content, cytochrome composition and cell wall structure (3,9,13,15,18,20). The most distinctive function of the symbiotic form of Rhizobium is the fixation of atmospheric nitrogen which requires the expression of the nitrogenase proteins plus those enzymes necessary to provide low potential electrons and energy in the form of MgATP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bra&-bixobizlm symbiosis is unique in that the bacteroids accumulate C in this form under conditions which are considered energylimiting (Karr e t al., 1984) and PHB formation may even compete with nitrogenase for energy (McDermott e t al., 1989). Karr et al (1984) found that PHB accumulation in B. japoniczlm begins with microaerophilic conditions and the p-ketolase activity parallels nitrogenase activity. A Tn5 site mutation in the nzjD or H region of Bjaponiczlm resulted in excess production of PHB (Hahn e t al., 1984).…”
Section: Introductionmentioning
confidence: 99%